Implikasi dan Pranggapan proses Negosiasi di Pasar Setonobetek Kota Kediri serta Penerapanya menurut Teks Negosiasi sebagai Bahan Ajar di SMAN 7 Kota Kediri - Derana, Ganes Tegar; Suhaimi, Imam; Zahra, Alifarose Syahda (Adjektiva: Educational Languages and Literature Studies, 2022)
As social humans, we cannot do without communication activities. The purpose of this study is to find out how presumptions and verbal cues are used in community negotiations in the Setonobetek market, Kediri City for high school textbooks. The research method used is descriptive and qualitative. data collection and observation, interviews, recording and independent listening skills, engaging in dialogue and note-taking skills, and data analysis methods Myers and Huberman. The results of this study are (1) Speech presuppositions in the Setonobetek market negotiations, Kediri City, namely. Latent presuppositions inform the existence of a person, factual presuppositions inform an event, structural presuppositions of the unmentioned recipient are understandable, and lexical presuppositions indicate sentences. It refers to certain elements after the verb and the question mark. Presets and Non-factual Presets No counterfactuals were found in the negotiations at the Setonobetek market in Kediri, and (2) verbal implications in the negotiations at the Setonobetek market in Kediri. The Setonobetek Market of Kediri City is a traditional meaning that is universal so it is easy to understand. conversational meaning Provide temporary meaning, (3) use the results of presuppositions and analysis of meaning as teaching materials. The text in the form of handouts is based on core competencies and basic competencies in the 2013 syllabus. Conclusion There are Verbal Presumptions and Suggestions in Negotiations in the Setonobetek Market Community, Kediri City as a Textbook High School Student